Improving the Profile of Pancasila and Skills through the Integration of Project and Problem-Based Learning - Suardi, Suardi; Hashim, Shahrin Bin; Firdaus, Firdaus; Syarifuddin, Syarifuddin; Nur, Rahmat; Nur, Hasruddin; Nur, Syahban; Marsuki, Nur Riswandy; Ramlan, Herdianty; Mutiara, Indah Ainun; Muchtar, Fitri Yanty (Universitas of Muhammadiyah Makassar, 2024)
Developing Pancasila student profile dimensions and 21st-century skills remains a significant challenge in modern education. This study aims to enhance 21st-century skills and strengthen the Pancasila student profile by integrating Project-Based and Problem-Based Learning methodologies grounded in research and community service. A mixed-methods approach was employed, with qualitative data collected from three informants selected through purposive sampling and quantitative data gathered from 68 respondents using total sampling. Data collection methods included questionnaires, observations, interviews, and documentation. Qualitative data is analyzed through the stages of reduction, display, and conclusion, while quantitative data is processed using descriptive statistics and correlation analysis through JASP software. Triangulation was applied to ensure the validity of the qualitative data, and statistical tests were used for the quantitative data. The results indicate that integrating project-based and problem-based learning in the Social Sciences Learning course, Research Methods, and Social Statistics significantly enhances the dimensions of the Pancasila student profile while improving 21st-century skills. This study highlights the effectiveness of combining innovative learning models to foster students' character and skill development.